2016
DOI: 10.1165/rcmb.2015-0227oc
|View full text |Cite
|
Sign up to set email alerts
|

IL-13 Inhibits Multicilin Expression and Ciliogenesis via Janus Kinase/Signal Transducer and Activator of Transcription Independently of Notch Cleavage

Abstract: Loss of ciliated cells and increases in goblet cells are seen in respiratory diseases such as asthma. These changes result in part from reduced differentiation of basal progenitor cells to ciliated cells during injury and repair. The T helper 2 cytokine, IL-13, has been shown to inhibit ciliated cell differentiation, but the mechanism is not clearly understood. We recently showed that Notch signaling inhibits ciliated cell differentiation in submerged culture by repressing multicilin and forkhead box J1 (FOXJ1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 40 publications
(61 reference statements)
0
13
0
Order By: Relevance
“…Conflicting data have been reported on dependence of IL13-induced goblet cell metaplasia on NOTCH signalling in ex vivo cultured PBECs 25,46 . Our data on freshly isolated bronchial epithelial cells show that expression of NOTCH2 and Notch target genes is present in goblet cells from healthy controls only, and absent from ciliated, mucous ciliated and goblet cells in asthmatic airway wall.…”
Section: Discussionmentioning
confidence: 99%
“…Conflicting data have been reported on dependence of IL13-induced goblet cell metaplasia on NOTCH signalling in ex vivo cultured PBECs 25,46 . Our data on freshly isolated bronchial epithelial cells show that expression of NOTCH2 and Notch target genes is present in goblet cells from healthy controls only, and absent from ciliated, mucous ciliated and goblet cells in asthmatic airway wall.…”
Section: Discussionmentioning
confidence: 99%
“…Because Notch signaling inhibits ciliated cell differentiation in vitro by repressing multicilin and forkhead box J1, 165 low Notch levels might suggest increased ciliogenesis, but this was not the case. However, it has been shown that IL-13 inhibits ciliated cell differentiation independent of Notch signaling, 166 suggesting 2 distinct signaling pathways can affect ciliated cell differentiation, which might be of relevance in the different SCs of severe asthma. The other SCs showed some overlap with SC2, but each exhibited distinct profiles illustrating the heterogeneity of the epithelial gene signature across the spectrum of asthma severity.…”
Section: Epithelial Clusters and Asthma Heterogeneitymentioning
confidence: 99%
“…In contrast to this finding, the overexpression of either Notch1 or Notch3 has been shown to drive goblet cell metaplasia in a system devoid of inflammatory cytokines such as IL-13 (Gomi, Arbelaez, Crystal, & Walters, 2015). This indicates that different Notch isoforms impact on GCD both within IL-13-high and IL-13-low environments (Gerovac & Fregien, 2016;Gomi et al, 2015;Guseh et al, 2009).…”
Section: Role Of Notch In Gcdmentioning
confidence: 90%
“…Binding of the NICD to RBPJ is well documented to activate the transcriptional repressors hairy and enhancer-of-split (HES) and hairy and enhancer-ofsplit related with YRPW motif (HEY) (Fischer & Gessler, 2007), which repress airway ciliogenesis (Gerovac et al, 2014;Tsao et al, 2009). Notch signaling also represses expression of multicilin (MCIDAS) and forkhead box J1 (FOXJ1) in airway epithelium, which in turn inhibits ciliated cell differentiation (Gerovac et al, 2014;Gerovac & Fregien, 2016). Additionally, recent cell lineage tracing studies have highlighted Notch as a key regulator of epithelial trans-differentiation in the adult lung (Lafkas et al, 2015).…”
Section: Role Of Notch In Gcdmentioning
confidence: 99%